PRAKTIK GHARAR DALAM TRANSAKSI JUAL BELI GABAH DI DESA LAHOTUTU KECAMATAN WONGGEDUKU BARAT KABUPATEN KONAWE - Haliq, Muhammad Ripal (Fakultas Syariah IAIN Kendari, 2022)
The grain sale and purchase transaction in Lahotutu Village occurs after harvest, where the buyer and farmer offer an agreement on the grain sale and purchase transaction, after agreeing on the price and time of payment, the grain will be transported directly to the processing plant. Payment methods are done in two ways, cash and deferral. Payments by deferral are often made by farmers and grain buyers, but in the grain sale and purchase contract, which is carried out only using a verbal agreement, it is not written when the payment will be made. Then the buyer can not clearly determine the time of payment. This has the potential to result in a dispute between the two parties and contains an element of ambiguity. The purpose of this study was to determine the practice of buying and selling grain in Lahotutu Village, as well as to determine the practice of gharar in grain buying and selling transactions in Lahotutu Village. This research method is a qualitative research with the type of field research (field research) using an empirical approach, the data sources in this study are secondary and primary data. The collected data were analyzed using deductive thinking. The results of this study indicate that the practice of buying and selling grain between farmers and buyers is carried out after harvest, after both parties agree on the price and time of payment, then payments are made in cash and are deferred but are more likely to be deferred and the buyer cannot determine the time of payment clearly. The perspective of Islamic law on the practice of gharar in buying and selling grain in Lahotutu Village, namely: a). The contract contains the potential for gharar because there is no clear binding contract in writing, b). From the object of the contract there is no problem because it avoids the potential for gharar, c). The suspension of payment time contains many elements of ambiguity (gharar) such as the determination based on the day, week, after the rice is sold, and based on the weather.Keywords: Gharar, Buy and sell, Grain